Evaluation of physiotherapy students' attitudes and engagement with social networking and eLearning systems: implications for education and training. (2nd April 2022) - Pepera, Garyfallia; Dimitriadis, Zacharias; Antoniou, Varsamo; Strimpakos, Nikolaos; Kapreli, Eleni
Social Networking Sites (SNSs) use increase tremendously among university students, creating at the same time second thoughts and opportunities for their use. This study explored, for the first time, the impact of Social Networking Sites and eLearning platform (eClass) on the education and academic life of Greek students. An online 35-statement questionnaire was administered to 330 undergraduate students of the Physiotherapy Department at the University of Thessaly. Demographic data, nature of SNSs, their application into education, and the use of e-Learning platform (eClass) were collected and analysed. The results revealed the high familiarity of university students with SNSs, the acknowledgment of the potential negative effects of their excessive use and their importance for communication and education purposes, proposing reforms that would embed the use of social media in teaching and learning pedagogies across academic disciplines.